The influence of school environment on gender equality in student participation - Yusuf, Frida Maryati; Utina, Ramli; Haruna, Moh. Fahri; Handayani, Lenny (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2025)
This descriptive quantitative study aims to examine the perceptions of gender equality among students at SMA Negeri (State Senior High School) 1 Bunta. Data were obtained from 119 students who completed a 75-item questionnaire. The analysis employed descriptive statistics, yielding an average perception score of 238,99 with a score range of 63-300. The principal finding indicates that teachers’ treatment of students based on gender is the most prominent factor in supporting gender equality within the school environment, reflected by the highest percentage of 81,28 %.  However, cultural aspects, social norms, and formal school policies still require greater attention to overcome existing barriers.  The study recommends strengthening pro-gender equality school policies, providing gender‑awareness training for teaching staff, and developing programs that encourage active student participation without discrimination.  The implications of the findings are expected to serve as a basis for policymakers in creating an inclusive and fair educational environment for all genders.